Causal role of immune cells in psoriasis: a Mendelian randomization analysis - Wang, Anning; Zhang, Jingyuan (Frontiers in Immunology, 2024)
Background: A growing body has shown that immune cells are linked to psoriasis. It is, however still unclear if these associations reflect a relationship of cause and effect. Objective: We employed a two-sample mendelian randomization (MR)-based study to elucidate the probable causative connection between immune cells and psoriasis. Methods: Summary information for psoriasis (Ncase = 5427, Ncontrol = 479171) was obtained from the European Bioinformatics Institute. Summarized statistical information on 731 immune cell features including morphological parameters (MP; n = 32), relative cell number (n = 192), median fluorescence intensity (MFI) of surface antigens (n = 389), and absolute cell number (n = 118) was obtained from the Genome-Wide Association Studies (GWAS) catalog. The research consisted of forward MR analysis, in which immune cell traits were used as the exposure factor and psoriasis was the outcome, as well as reverse MR analysis, in which psoriasis was used as the exposure factor and immune cell traits were the outcome. We ran numerous sensitivity analyses in order to ascertain the study results for robustness, heterogeneity, and potential multiple-biological effects.Result: This research determined a probable causative connection between immune cells and psoriasis.In particular, we identified 36 distinct types of immune cells that are potentially causally linked to psoriasis. Conclusion: Our findings indicate causal strong correlations between 36 immunological phenotypes and psoriasis, thus directing future clinical trials.